Aplicación del proceso de atención de enfermería en paciente adulta con embarazo ectópico abdominal a término en el área de obstetricia del Hospital Sagrado Corazón de Jesús período 2018-2019 - Cedeño Párraga, Narcisa Stefania (2020)
Abdominal ectopic pregnancy is a very serious problem that we have in our society. About 2% of pregnancies end up being ectopic. By definition an ectopic pregnancy is a pregnancy that is implanted outside the walls of the womb, but can also be implanted in the ovary or in the walls of the intestine. Around 800 to 1000 women die every year because of this disease. Therefore, the clinical case was developed in a 35-year-old patient, a 37-week-old patient, presenting a diagnosis of full-term abdominal ectopic pregnancy. He went to the Sacred Heart of Jesus Hospital in the City of Quevedo for the presence of symptoms such as: persistent abdominal pain on the right side, vaginal bleeding, vomiting, lightheadedness and fainting. The nursing staff had to carry out the corresponding medical evaluations during the pre-operative and post-operative to the patient to verify that there is no complication before the caesarean section. During the post-operative period, the patient presented symptoms of nausea, so the nurse intervened in a timely manner by providing medications to relieve nausea, educational talk about the food that should be consumed to relieve and avoid discomfort. He also verified that the vital signs and hemoglobin are in normal values, found that under the medication prescribed by the doctors the vaginal bleeding has stopped. The descriptions of the medical interventions were made through the use of the NANDA, NIC, NOC taxonomies, since, thanks to their classification, the most convenient decisions were determined to achieve the expected results.